The influence of Work Discipline and Quality Of Work Life toward Employee Performance at PT Jasa Raharja (Persero) Kantor Cabang Jawa Tengah - Hervindi Resta Pratiwi; Endang - Sulistiyani (Politeknik Negeri Semarang, 2021)
PT Jasa Raharja (Persero) Branch of Central Java is a company engaged in the field of social insurance business owned by the Republic of Indonesia in the Central Java region. This research aims to determine the effect of work discipline and quality of work life on the employee performance of PT Jasa Raharja (Persero) Branch of Central Java. The data collection methods used in this research are observation and questionnaires which were distributed to 39 employees of PT Jasa Raharja (Persero) Branch of Central Java using saturation sampling. The methods of data analysis used are validity test, reliability test, classic assumption test, multiple linear regression test, t test, F test, and coefficient of determination,. The results of this research shows that work discipline and quality of work life have positive and significant effect both partially and simultaneously on the employee performance. The result of the analysis obtained Adjusted R2 value is 0,423, it means that the contribution of independent variables in influencing the dependent variable is 42,3% while the remaining 0,577 or 57,7% is influenced by other factors which are not examined in this research.